The relationship between talent management practices and retention of generation 'Y' employees: mediating role of competency development. Issue 1 (1st January 2020) - Younas, Minha; Bari, Muhammad Waseem
Abstract: In a competitive marketplace, retention of talented and younger employees is a challenge for organizations. Thus, it becomes important for organizations to execute employees' development strategies to retain Generation Y employees. The goal of this research is to analyze the effect of talent management (TM) practices i.e. mentoring, strategic leadership, social media, and knowledge sharing on the intention to stay of generation Y employees and strengthening this relationship by investigating the mediating role of competency development. A total of 372 employees of generation Y participated in the study. The data were analyzed through the PLS-SEM model using smartPLS-3 software. Findings reveal that TM practices: mentoring, strategic leadership, social media positively affect the intention to stay of generation Y employees, while knowledge sharing has no significant effect on the intention to stay. Competency Development mediates the relationship between strategic leadership, social media, knowledge sharing and intention to stay. However, competency development does not significantly mediate the relationship between mentoring and intention to stay.